NEOVASCULAR COMPLICATIONS FROM CYTOMEGALOVIRUS NECROTIZING RETINOPATHY IN PATIENTS AFTER HAPLOIDENTICAL HEMATOPOIETIC STEM CELL TRANSPLANTATION. Issue 7 (July 2021) - Long, Ze; Hou, Jing; Miao, Heng
Abstract : Purpose: To report the incidence and clinical features of neovascular complications from cytomegalovirus (CMV) necrotizing retinopathy in patients after haploidentical hematopoietic stem cell transplantation. Methods: Thirty-nine patients (58 eyes) of CMV necrotizing retinopathy after haploidentical hematopoietic stem cell transplantation in our institute between January 2018 and June 2020 were retrospectively reviewed, and cases that developed neovascular complications during follow-up were identified and described. Results: Two (2 eyes) cases that developed neovascular glaucoma from CMV necrotizing retinopathy were identified. Both of them manifested as granular peripheral retinitis, panretinal occlusive vasculitis, and some degree of intraocular inflammation, which were consistent with chronic retinal necrosis. Insidious progression of isolated immune-mediated occlusive vasculitis that could only be observed on fundus fluorescein angiography without active retinitis or intraocular inflammation was recognized to be the cause in one of two cases. Conclusion: Neovascular glaucoma developed in 5.1%/cases and 3.4%/eyes complicated by CMV chronic retinal necrosis and vasculitis in patients after haploidentical hematopoietic stem cell transplantation, which warrants the needs for long-term follow-up. Immune-mediated CMV vasculitis could be an isolated manifestation in patients with a minimal immune deviation and may only be found on fundus fluorescein angiography, which emphasizes the importance of fundus fluorescein angiography on a regular basis during follow-up. Abstract : Neovascular complications from cytomegalovirus necrotizing retinopathy developed in 5.1%/cases and 3.4%/eyes in patients after haploidentical stem cell transplantation. Immune-mediated cytomegalovirus vasculitis could be an isolated manifestation in patients with a minimal immune deviation, which could only be found on fluorescein angiography and warrants the needs for long-term follow-up.